Design and rationale for RE-VERSE AD: a phase 3 study of idarucizumab, a specific reversal agent for dabigatran - Pollack, Charles V.; Reilly, Paul A.; Bernstein, Richard; Dubiel, Robert; Eikelboom, John; Glund, Stephan; Huisman, Menno V.; Hylek, Elaine; Kam, Chak-Wah; Kamphuisen, Pieter W.; Kreuzer, Joerg; Levy, Jerrold H.; et al. (Thrombosis and haemostasis, 2015)
Idarucizumab, a Fab fragment directed against dabigatran, produced rapid and complete reversal of the anticoagulation effect of dabigatran in animals and in healthy volunteers. The Study of the REVERS al E ffects of Idarucizumab in Patients on A ctive D abigatran (RE-VERSE AD™) is a global phase 3 prospective cohort study aimed at investigating idarucizumab in dabigatran-treated patients who present with uncontrollable or life-threatening bleeding, and in those requiring urgent surgery or intervention. We describe the rationale for, and design of the trial (clinicaltrials.gov NCT02104947).